Colombia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix analyzes economic developments in Colombia during 1996-99. Output growth slowed sharply in 1996 and early 1997, but subsequently rebounded owing to stronger exports, a temporary boom in world coffee prices, and an easing of credit policy. Despite efforts at addressing the fiscal imbalances, the nonfinancial public sector deficit widened further to more than 4 percent of GDP in 1997. Monetary policy during 1996 and most of 1997 was geared toward stimulating domestic demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet